Identification of Defects in Electronic Component Products: Case Study at PT Omron Manufacturing of Indonesia - Rizqi Mabul Sururi Rizqi Mabul Sururi (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
The identification of product defects at PT Omron Manufacturing of Indonesia is motivated by the large number of defect discoveries in the January-October 2023 period, these defects cause considerable losses, namely the number of product parts disposed of in the amount of 3591. Based on these problems, the purpose of this research is to identify the causes of defects and formulate alternative solutions for continuous improvement. Identification of defects using the Pareto diagram method, fishbone analysis, and failure mode and effect analysis (FMEA), after getting the cause with the highest risk of priority number (RPN) value, the next step is to find alternative solutions using the 5W + 1H kaizen approach. The output generated from this research is daily checklist maintenance for operators and weekly checklist maintenance for the productive maintenance department.